EFFECTIVE CLASSROOM MANAGEMENT DURING THE LIMITED FACE-TO-FACE LEARNING PERIOD IN JUNIOR HIGH SCHOOL MEDAN - Sihombing, Rizky Agassy; Muslim, Muslim; Rahman, Taufik (Universitas Negeri Yogyakarta, 2023)
This research addresses the challenges posed by the Covid-19 pandemic to education, particularly the limitations of online learning and the subsequent implementation of limited face-to-face learning. Recognizing the significant impact of these challenges on both teachers and students, the study aims to explore factors influencing the efficiency of classroom management during limited face-to-face learning. Focusing on 8th-grade students at SMP Negeri 2 Percut Sei Tuan, the research utilizes a quantitative approach, employing a Likert scale questionnaire distributed to 15 students via Google Form. The key findings reveal a deficiency in creating a conducive learning climate (32% - Not good), with challenges stemming from limited physical interaction, technological barriers, and difficulties in maintaining student engagement. However, organizing the study room received positive responses (67.5% - Good), indicating effective physical layout and orderliness contributing to a conducive learning atmosphere. On the other hand, managing the interaction of teaching and learning activities scored lower (30% - Not good), highlighting challenges related to varied teaching methods, learning media, and active student participation. In conclusion, the research underscores the necessity for improvements in the classroom management process within the limited face-to-face learning context. The findings provide valuable insights for enhancing teaching strategies, fostering a more conducive learning environment, and ultimately contributing to the successful attainment of learning objectives within the constraints of limited face-to-face interactions. The study's implications extend to educators, researchers, and policymakers seeking to optimize the learning experience in the unique circumstances brought about by the pandemic.